Pengaruh Konten Kreator dan Storytelling Digital Pada Brand Image Kosmetik Lokal di Jabodetabek Studi Kasus Brand Somethinc - Thamrin , Hendi; Santoso, Thomas William (Besaung : Jurnal Seni Desain dan Budaya, 2025)
In today's digital era, content creators and Storytelling play a crucial role in building and strengthening brands. Content creators enhance trust and brand reach, while Storytelling creates emotional connections and reinforces brand identity. This study aims to analyze the integrative influence of content creators and digital Storytelling strategies on the enhancement of brand image for local cosmetics, particularly the Somethinc brand, in the Jabodetabek  area. Using quantitative and qualitative methods, this research examines how strategic collaboration between content creators and digital narratives can strengthen brand perception in the eyes of consumers. Data were collected through surveys and in-depth interviews with consumers and industry players. The results indicate that the integration of content creators and digital Storytelling significantly impacts brand image enhancement. Engaging content and resonant narratives can build strong emotional connections with consumers, thereby enhancing brand image. This study provides valuable insights for local cosmetic brands in designing more effective and resonant digital marketing campaigns. The theoretical contributions of this research are significant for the digital marketing literature and are relevant for practitioners in the cosmetics industry looking to strengthen brand image through digital strategies.